TINJAUAN UMUM TENTANG CERITA RAKYAT TRADISIONAL DAN MAKNANYA (KAJIAN FOLKLOR) - Redi Saputra; Ahmad Syakib Arselan (STKIP Pesisir Selatan, 2025)
The themes of traditional folktales are extremely diverse. Some focus on the creation of the world, while others tell of heroes, gods, or mythological beasts. Overview of Traditional Folktales and Their Meanings (Folkloric Studies) discusses traditional folktales and their meanings. This article aims to provide a better understanding of folklore and its benefits to people's lives. This journal discusses the definition of folklore, types of folklore, characteristics of folklore, meanings in folklore, and functions of folklore. In addition, this article also discusses folklore studies, including the definition of folklore, the history of folklore development, theories of folklore, and folklore studies in Indonesia. This article uses the method of literature study, data analysis, and data presentation systematically and objectively. This article can provide benefits for readers, such as gaining a better understanding of folklore, finding truth values, getting exemplary examples, developing fantasy, sharpening intelligence, and fostering interest in reading. This article can also provide benefits for the development of science and community life, such as a source of information, reference material, and guidelines in decision making.